PENGARUH STATUS SOSIAL EKONOMI TERHADAP KEJADIAN BAYI BERAT LAHIR RENDAH (BBLR) DI KELURAHAN GEDUNG JOHOR KOTA MEDAN - Surya Anita; Dewi R Bancin; Sitorus, Friska (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
LBW is a baby with a low birth weight or less than 2500 grams, birth weight is a good predictor of baby's growth and survival. A full-term baby is generally born weighing 2500 grams or more. LBW is one of the risk factors that contribute to infant mortality, especially during the perinatal period. The incidence and mortality of LBW due to complications such as asphyxia, infection, hypothermia, hyperbilirubinemia are still high (Indrayani, 2015). This study aims to see whether there is an effect of socioeconomic status on the incidence of LBW with the type of analytic observational research and cross sectional research design. The number of samples in this study were 62 people consisting of postpartum women who gave birth to LBW or not, the results showed that there was a link between socioeconomic status and the incidence of LBW where the PValue was (0.005), this study recommends that every pregnant woman should still consume foods that are nutritious though not expensive food.